THE CORRELATION AMONG KNOWLEDGE, ATTITUDE AND MOTHER’S BEHAVIOR IN ORAL AND DENTAL HEALTH CARE - Ni Nengah Arini Murni; Suwanti Suwanti (Jurnal Kesehatan Prima, 2017)
Abstract : The study aimed to determine the correlation among knowledge and attitude with the behavior of pregnant women in dental and oral health care during pregnancy. The research was analytic observational and in terms of time used crossectional approach. The population in this study were pregnant women at Narmada Community Health Center whereas the sample obtained by 34 people who came to check Antenatal Care (ANC) in June 2015 taken by accidental sampling technique. Data collection of knowledge, attitude and behavior variables used questionnaire and Statistical analysis was performed by using Chi Square test. The research finding indicated that from 34 respondents, 17 pregnant women (50%) had lack knowledge level about oral and dental health care during pregnancy. The attitude of pregnant women in dental and oral care during pregnancy was 73.5% (poor attitudes), and in terms of respondents’ behaviour was the same like respondents’ attitude by 73.5% (poor attitude). Therefore, it can be concluded that there was a significant correlation between knowledge with pregnant women behavior in dental and oral health care (P value = 0.013) and there was significant correlation between attitude with respondents behaviour in oral and dental care during pregnancy (P value = 0.004). Suggestion: It is expected for Health Care Institutions and health workers need to do an effort of sustainable counselling to communities, especially pregnant women about risk factors that can cause dental caries which can affect the health of both fetus and mother, increasing promotive efforts, for instance the improvement and maintenance of health and preventive efforts for communnities and pregnant women in order to have a good knowledge and attitude in maintaining oral an dental health care during pregnancy can be preserved and further enhanced, hence the sense of responsibility in terms of a behavior in the community or pregnant women concerning dental and oral health increases in line with knowledge improvement and developing attitudes.